(untitled) (Bangladesh Journal of Botany, 2023)
In the present study the essential oil components of the flowers and leaves of Amanus sage Pholomis longifolia var. longifolia boiss. & Bl by ultrasonic extraction and steam distillation method were determined. According to the chemical composition analysis of Amanus Sage plant using ultrasonic extraction method, major components were methyl-7-octadecenoate (69.02%) and methyl elaidate (16.87%). The essential oil contents of flowers and leaves of the Amanus sage plant were also determined by steam distillation method. When the essential oil components of the flower were examined, the main components were found to be tricosane (22.39%), caryophyllene (22.17%), alpha-cubebene (14.4305), beta-farnesene (7.7%) and linalool (4.69%). On the other hand the main components in the the leaves were caryophyllene oxide (27.20%), fenchone (18.63%), 1,8-cineole (6.12%), camphor (4.82%), and alpha-cubebene (4.11%). Bioactive properties of the components of Amanus sage obtained from both the ultrasonic extraction and steam distillation methods showed that this plant has important medicinal and aromatic properties. Bangladesh J. Bot. 52(2): 799-803, 2023 (September)